偶像、粉丝、养成 ： 韩国真人秀在中国的传播与影响 = A study of the influence and impact of South Korea reality shows in China - 蔡绮芸 Chua, Qi Yun (Nanyang Technological University, 2020)
真人秀最初源自欧美地区，但近几十年来韩国异军突起，所制作的真人秀对全球影响甚广，其中包括近五年来最流行的养成类真人秀。养成类真人秀最早起源于日本并兴于韩国，2018 年普及中国，并且伴随着新媒体时代的崛起，信息涵盖面日益宽广，此类节目的粉丝在真人秀的话语权也越来越大，这在中国当地逐渐引发热议。本文从文图学的角度分析了两个个案 —— 韩国《Produce 101》第二季与中国《偶像练习生》，从节目模式、视觉艺术等内容，来探讨商业群体如何利用粉丝追星的心理来引导现阶段的粉丝文化和粉丝经济的形成。在了解韩国真人秀的发展史、追朔韩国真人秀在中国的起源发展之后，笔者发现，韩国真人秀在中国深受欢迎是因为两国之间有着共同的文化。韩国真人秀聚焦于艺人的特质，而中国引进韩国版权后，在此基础上做出改编来符合中国观众的口味。真人秀节目把偶像与粉丝联系起来，通过各个偶像粉丝群体的组成建立粉丝忠诚度，再把这种忠诚度转化为商机，形成一种独特的消费模式，这也是现在粉丝追星的主要形式。 The concept of ‘reality show’ initially originated from western countries, yet South Korea soon caught up with the trend and became a gamechanger, producing sensational reality shows that are globally renowned. Amongst those reality shows, Idol Cultivation reality show is one of them, it is a type of reality show that originated from Japan and it first gained its popularity in South Korea. Later in 2018, Idol Cultivation reality shows also became a trend in China. Besides, it is worth noticing that fans of such shows are becoming increasingly prominent due to the rise of new media, allowing for wider coverage of information. This thesis uses Text and Image Studies to analyse two reality shows, Produce 101 Season 2 from Korea and Idol Producer from China. By looking at the show’s content, show’s visuals and more perspectives, this thesis seeks to understand how these shows attracted fans and how business communities tapped on show’s fanbase to form ‘fan economy’. By investigating the development process of Korean reality shows in China, it was discovered that the reason for Korean reality shows to gain popularity in China, was the existence of common culture between the two countries. Also, Korean reality shows are better in terms of displaying the artists’ traits, in which China has adapted to suit Chinese audiences' tastes. Another notable point is that reality shows connected idols to fans and maintained fans’ loyalty through the establishment of fan clubs, then transformed this loyalty into business opportunities, forming a fan economy.